Respuesta :
We must translate the equation from y-y1=m(x-x1) to ax+by=c from.
Distribute the 2 into x and 1
y+4=2x+2
Combine like terms and move terms:
-2x+y=-4+2
Simplify:
-2x+y=-2
-2x+y=-2 is in standard form
Distribute the 2 into x and 1
y+4=2x+2
Combine like terms and move terms:
-2x+y=-4+2
Simplify:
-2x+y=-2
-2x+y=-2 is in standard form
Answer:
[tex]\textsf{A.} \quad -2x + y = -2[/tex]
Step-by-step explanation:
[tex]\boxed{\begin{minipage}{5.5 cm}\underline{Standard form of a linear equation}\\\\$Ax+By=C$\\\\where:\\ \phantom{ww}$\bullet$ $A, B$ and $C$ are constants. \\ \phantom{ww}$\bullet$ $A$ must be positive.\\\end{minipage}}[/tex]
Given equation:
[tex]y + 4 = 2(x + 1)[/tex]
Distribute the right side of the equation:
[tex]\implies y+4=2x+2[/tex]
Subtract 2 from both sides:
[tex]\implies y+4-2=2x+2-2[/tex]
[tex]\implies y+2=2x[/tex]
Subtract y from both sides:
[tex]\implies y+2-y=2x-y[/tex]
[tex]\implies 2=2x-y[/tex]
Switch sides:
[tex]\implies 2x-y=2[/tex]
Therefore, the equation of the line written in standard form is:
[tex]\boxed{2x-y=2}[/tex]
Since this is not one of the answer options, switch the signs:
[tex]\implies -2x+y=-2[/tex]
Please note that this is not in standard form, since the coefficient of the term in x is negative. However, as the equation in strict standard form is not a given answer option, the only answer can be -2 + y = -2.